2017
DOI: 10.1002/asl.791
|View full text |Cite
|
Sign up to set email alerts
|

The underestimated magnitude and decline trend in near‐surface wind over China

Abstract: This study reports the magnitude, spatial pattern and temporal trend of near-surface wind speed (NWS) by comparing 20th century simulations in Coupled Model Intercomparison Project phase 5 (CMIP5) and 3 (CMIP3) and the climate reanalyses with measurements at 563 weather stations in China over 1961-2005. Both CMIP5 and CMIP3 agree quite well with observations in reproducing the spatial pattern of annual mean NWS. CMIP5 models are superior to CMIP3 models in hindcasting the magnitude and spatial pattern of seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(40 reference statements)
0
8
1
Order By: Relevance
“…Generally, the surface wind speed trends are not well simulated by the CMIP3 (Jiang, 2009), CMIP5 (Chen et al, 2012; Tian et al, 2019), and the new generation models of CMIP (CMIP6), which is maybe caused by the following: (1) The surface boundary conditions of CMIP GCMs do not include surface roughness, which can increase the friction force on the surface and weaken the wind speed due to urbanization, the trees and forest, and other types of underlying surface (Vautard et al, 2010), and (2) the current GCMs have a relatively low ability to represent some features of the atmospheric flow (Chen et al, 2012). For example, the CMIP5 GCMs fail to reproduce the slowed East Asia monsoon (Saha et al, 2014), which may result in the decline trend of surface wind speed in China (Jiang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the surface wind speed trends are not well simulated by the CMIP3 (Jiang, 2009), CMIP5 (Chen et al, 2012; Tian et al, 2019), and the new generation models of CMIP (CMIP6), which is maybe caused by the following: (1) The surface boundary conditions of CMIP GCMs do not include surface roughness, which can increase the friction force on the surface and weaken the wind speed due to urbanization, the trees and forest, and other types of underlying surface (Vautard et al, 2010), and (2) the current GCMs have a relatively low ability to represent some features of the atmospheric flow (Chen et al, 2012). For example, the CMIP5 GCMs fail to reproduce the slowed East Asia monsoon (Saha et al, 2014), which may result in the decline trend of surface wind speed in China (Jiang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the climatology of the East Asian winter monsoon simulated by 41 CMIP5 and 24 CMIP3 GCMs, Wei et al (2013) revealed that CMIP5 models perform better in simulating the near‐surface wind speed. Jiang et al (2017, 2018) and Jiang, Luo, and Zhao (2009) applied CMIP3 and CMIP5 GCMs to validate and project the surface wind speed over China, and the results show that these GCMs can capture the spatial patterns of annual and seasonal mean wind speed, but underestimate their decline trends.…”
Section: Introductionmentioning
confidence: 99%
“…Future changes in NWS over China have also been investigated. For example, Jiang et al [14,15] applied CMIP3 and CMIP5 databases to validation and projection of future NWS over China, and they found that CMIP3 and CMIP5 GCMs could realistically capture the spatial patterns of annual and seasonal mean wind speed, but that they tended to underestimate the trends of decline. Abolude et al [16] assessed the potential status of future wind power over China using CMIP5 models.…”
Section: Introductionmentioning
confidence: 99%
“…This may affect projections of future surface winds and associated fluxes over land surfaces. Climate simulations in the Coupled Model Intercomparison Project Phase 3 and 5 (CMIP3 and CMIP5) generally underestimate the rate of decline in surface wind speed by an order of magnitude (Jiang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms related to the observed wind stilling are not well understood (Wu et al 2018, Zeng et al 2018. Moreover, climate models have limited ability for simulating the long-term trend in surface wind speeds (Jiang et al 2017, Tian et al 2019, indicating the need for a clear understanding of the mechanisms of wind stilling.…”
Section: Introductionmentioning
confidence: 99%